The Kola Peninsula: Geography, History and Resources - Luzin, Gennady P.; Pretes, Michael; Vasiliev, Vladimir V. (ARCTIC, 1994)
The Kola Peninsula in northwest Russia is one of the most important economic regions in the circumpolar North. The region contains valuable natural resources, including a wide variety of mineral and fish resources, and is proximate to the large gas fields of the Barents Sea. A large population, industrial complexes, and military infrastructure are also characteristic of the region. The Kola Peninsula developed rapidly during the Soviet period (1917-92) under the principles of socialist development policy. This policy favoured extensive resource extraction and industrialization and resulted in increased northern settlement, much of it involuntary. Soviet development policy prompted the opening of new mines and the construction of smelters and refining facilities, while Soviet military policy necessitated the establishment of large military basing operations. Resource development and processing have led to severe environmental damage in the region and beyond. This paper describes the geographical features of the Kola Peninsula and the region's development history and contains data on natural and labour resources.Key words: Kola Peninsula, Murmansk Region, Murmansk, Russian Arctic, Soviet Arctic, natural resources, economic development, militarization La presqu'île de Kola dans le nord-ouest de la Russie est l'une des plus importantes zones économiques du Grand Nord circumpolaire. La région contient de précieuses ressources naturelles, y compris une grande variété de ressources minières et de poisson, et elle est proche des champs gaziers de la mer de Barents. Cette région se caractérise aussi par une forte population, ainsi que par la présence de complexes industriels et d'une infrastructure militaire. La presqu'île de Kola s'est développée rapidement au cours de l'ère soviétique (1917-1992), selon les principes des politiques socialistes de développement. Ces dernières, qui mettaient l'accent sur une intensification de l'exploitation des ressources et de l'industrialisation, ont accru la colonisation - en ...